2021
DOI: 10.1002/agj2.20729
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and forecasting of soybean yield using artificial neural networks

Abstract: In science, estimation is the calculation of a current value, while forecasting (or prediction) is the calculation of a future value. Both estimation and forecasting are based on covariates. However, whereas estimation enables greater agility in current decision making, forecasting can reveal different strategies for the future. The use of Artificial Neural Networks (ANNs) has brought improvements in accuracy to the estimation and forecasting of agricultural yield for various crops around the world. These mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Using another strategy, maize yield prediction was performed with machine learning with different models, and the best of them, Stacked LASSO, presented a Mean Bias Error (MBE) of 53 kg/ha and a Relative RMSE (RRMSE) of 9.5% [32]. For the soybean crop, annual productivity was predicted in the region of the Brazilian states of Maranhão, Tocantins, Piauí, and Bahia as a function of monthly climate variables (air temperature, precipitation, and global radiation) and water balance components (cultivation evapotranspiration, storage, actual cultivation evapotranspiration, water deficiency, and surplus) during plant development through a deep artificial neural network [33] with a dataset size of 920 examples, the obtained RMSE was 167.85 kg.ha −1 . The unprecedented differential in the strategy of using climatic variables subdivided into maize plant development stages that are differentially sensitive to water stress was assertive.…”
Section: Wwwetasrcom Duarte De Souza Et Al: Maize Yield Prediction Us...mentioning
confidence: 99%
“…Using another strategy, maize yield prediction was performed with machine learning with different models, and the best of them, Stacked LASSO, presented a Mean Bias Error (MBE) of 53 kg/ha and a Relative RMSE (RRMSE) of 9.5% [32]. For the soybean crop, annual productivity was predicted in the region of the Brazilian states of Maranhão, Tocantins, Piauí, and Bahia as a function of monthly climate variables (air temperature, precipitation, and global radiation) and water balance components (cultivation evapotranspiration, storage, actual cultivation evapotranspiration, water deficiency, and surplus) during plant development through a deep artificial neural network [33] with a dataset size of 920 examples, the obtained RMSE was 167.85 kg.ha −1 . The unprecedented differential in the strategy of using climatic variables subdivided into maize plant development stages that are differentially sensitive to water stress was assertive.…”
Section: Wwwetasrcom Duarte De Souza Et Al: Maize Yield Prediction Us...mentioning
confidence: 99%
“…A hybrid approach to integrating biophysical models and NN methods, known as physics-guided machine learning, has been used in fields such as hydrology and materials science (Willard et al (2020). While studies have shown that NN methods are effective predictors of agronomic targets, such as gross primary production (Peng et al, 2019) and yield (Barbosa dos Santos et al, 2021), studies that guide NNs with crop models are rare. One recent study has shown that machine-learning-based yield prediction can be improved with guidance from existing crop models (Shahhosseini et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…(2020). While studies have shown that NN methods are effective predictors of agronomic targets, such as gross primary production (Peng et al., 2019) and yield (Barbosa dos Santos et al., 2021), studies that guide NNs with crop models are rare. One recent study has shown that machine‐learning‐based yield prediction can be improved with guidance from existing crop models (Shahhosseini et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These models can automatically learn from data using a multi-layer architecture, learn from the hierarchical outputs of the previous layers, and deal with non-linearities between crop traits and yield estimation [ 31 , 43 , 44 ]. ML algorithms such as random forest and neural networks have been widely used to predict crop yield using data collected remotely [ 5 , 11 , 45 , 46 , 47 , 48 , 49 , 50 ]. It should be noted that the model accuracy is affected by the dates of the predictions [ 44 ], so it is important to consider this factor while making soybean yield predictions using satellite imagery.…”
Section: Introductionmentioning
confidence: 99%